Magnetic compression anastomosis for postoperative biliary atresia. Issue 6 (June 2017) - Matsuura, Rei; Ueno, Takehisa; Tazuke, Yuko; Tanaka, Natsumi; Yamanaka, Hiroaki; Takama, Yuichi; Nakahata, Kengo; Yamamichi, Taku; Maeda, Noboru; Osuga, Keigo; Yamanouchi, Eigoro; Okuyama, Hiroomi
Abstract: We report a case of successful magnetic compression anastomosis (MCA) for obstructed cyst‐jejunostomy in a young woman who had undergone surgery for type 1 biliary atresia (BA) on day 78 of life. A 16‐year‐old girl was admitted with obstructive jaundice. Jaundice resolved with percutaneous trans‐hepatic cholangiodrainage (PTCD) but contrast medium injected from the PTCD tube did not flow through the anastomosis. Magnets were placed on each side of the anastomosis, in the cyst and the jejunum, to compress the partition. On postoperative day (POD) 6, the anastomosis was recanalized and the PTCD tube placed trans‐anastomotically until POD 245. The patient remained free from jaundice after removal of the PTCD tube. MCA can be a useful and less invasive procedure for treating biliary tract anastomotic obstruction in patients with BA.